The Estimation of Seagrass Carbon Stock in North Lombok Coastal: GIS-Based Analysis - Farista, Baiq; Virgota, Arben; Ernawati, Ernawati; Widiyanti, Astrini (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Seagrass is a higher plant from the Anthophyta division that lives below the surface of the air in shallow marine environments. Seagrass ecosystems play a crucial role in carbon sequestration through photosynthesis, which absorbs carbon from the environment. This study aims to estimate carbon stocks in seagrass meadows along the coastal area of Pemenang District, North Lombok. The study was conducted from April to June 2024 using a geographic information system (GIS) approach combined with field observations. The sampling method used a GIS approach to determine the distribution and level of seagrass cover. Seagrass cover levels were classified into three classes: high, medium, and low. Seagrass samples were taken at each cover level and then analyzed in the laboratory to measure biomass and carbon content to estimate carbon stocks. The results showed that the total area of ​​ seagrass beds in Pemenang District reached 685.26 hectares, consisting of eight species, namely Enhalus acoroides, Thalassia hemprichii, Halodule pinifolia, Halodule uninervis, Halophila ovalis, Cymodocea rotundata, Cymodocea serrulata, and Syringodium isoetifolium. Halodule uninervis contributed the highest carbon stock (54.12 gC/m²), followed by Halodule pinifolia (53.22 gC/m²) and Thalassia hemprichii (51.16 gC/m²). The total seagrass carbon stock across the study area was 2.53 tons/Ha, with above-ground biomass at 0.826 tons/Ha and below-ground biomass at 1.7 tons/Ha, amounting to an estimated total of 1,735 tons of carbon. Spatial analysis indicated an even distribution of seagrass meadows along the Pemenang coastline.